The Effect of Complex Feed Supplements on the Growth and Development of Long Bones in Broilers - Semak , Anna; Cherepanova, Nadezda; Panov, Valeriy; Prosekova, Elena; Kubatbekov, Tursumbay (KnE Life Sciences, 2021)
Poultry farming as one of the most intensive branches of animal husbandry, and it uses a large amount of various feed supplements in order to obtain the maximum production volume. This article presents the results of a study on the effect of feed supplements used for feeding broiler chickens. Until the age of 42 days, the chickens received a phytase-containing enzyme supplement, mineral supplements Mn and Ca in a citrate form and a vitamin supplement of 1,25-dioxycholecalciferol (vitamin D3, calcitriol). The live weight of the chickens was measured at the age of 1, 4, 7, 14, 21, 28, 35 and 42 days. The femur development of the chickens was studied through morphological methods (morphometry and histological examination). The influence of various supplements (from the combined to the mutually absorbing ones) on the growth and development of the long bones of broilers was identified. Keywords: poultry, broilers, feed supplements, vitamin D, mineral supplements, enzyme supplements, histology, bones